2010
DOI: 10.1111/j.1778-428x.2010.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative optimization of oxygen delivery

Abstract: The concept of perioperative hemodynamic optimization was developed by Shoemaker in the early 1980s. The controversy concerning optimization of oxygen delivery persists as recent studies show that the timing of this optimization appears to be an essential factor. At the initial stage of aggression (operative period, initial phase of septic shock), optimization of volume replacement decreases morbidity and mortality, while at a later period excess volume replacement can be harmful for the patient. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
4
0
4
Order By: Relevance
“…In the medical literature there are studies that have shown the mismatch between transfusions and increased DO2 and VO2. This seems to suggest a predominant role of the CI in the maintenance of adequate DO2 and VO2 may redefine the limits and traditional criteria for the use of blood derivatives [24] , [25] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the medical literature there are studies that have shown the mismatch between transfusions and increased DO2 and VO2. This seems to suggest a predominant role of the CI in the maintenance of adequate DO2 and VO2 may redefine the limits and traditional criteria for the use of blood derivatives [24] , [25] .…”
Section: Discussionmentioning
confidence: 98%
“…To improve tissue oxygenation, although the mild anemia, patient was monitored with Vigileo™. Optimizing fluid administration using CI, SV and ScVO2 parameters, will help to maximize cardiac output and, therefore, oxygen delivery [10] , [11] .…”
Section: Discussionmentioning
confidence: 99%
“…El balance entre la DO 2 y la VO 2 es pilar para valorar el grado de perfusión tisular y el desarrollo de la disfunción de órganos múltiples en condiciones que favorecen la dO 2 (13)(14)(15) . En el estado estable, la VO 2 utiliza sólo 25% de la DO 2 .…”
Section: El Gasto Cardíaco Como Determinante De La Perfusión Tisularunclassified
“…Finally, the third article by Conte et al 3 . reviews another important subject in relation to optimization of oxygen delivery, which may also affect prognosis, especially that of the most seriously ill patients.…”
mentioning
confidence: 99%